Ekstraksi Polifenol Total dari Umbi Bawang Dayak (Eleutherine bulbosa [Mill.] Urb.) Menggunakan Metode Citric Acid-Glucose based Microwave Assisted Extraction - Selvy Jumiatul Astati; Mirhansyah Ardana; Islamudin Ahmad (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
The use of environmentally friendly solvent-based expulsion methods today began to be widely used, one of which is a microwave-assisted extraction (MAE) using a citric acid-glucose acid solvent. The study aims to determine the influence of the use of citric acid-glucose based microwave-assisted extraction against the total extraction of polyphenols from Dayak onion bulbs (Eleutherine bulbosa [Mill.] Urb.).The dried samples were extracted using a solvent (green solvent) citric acid – glucose with a ratio of 4:1, 5:1 and 6:1 g/g with the extraction conditions in the form of microwave strength of 50% for 10 minutes with a sample and solvent ratio of 1:10 g/mL, then Extract solution obtained further determination of the total levels of polyphenols using Folin ciocalteu reagents, and its absorption was measured using a UV-vis spectrophotometer at a wavelength of 791 nm. Based on the results of the study, the total amount of polyphenols obtained from each of the solvent conditions used against the samples was 21.92 mgGAE/g samples, 13.86 mgGAE/g samples, and 14.38 mgGAE/g samples. From this study, it can be concluded that the concentration of citric acid in the microwave-based citric acid-glucose method is assisted by extraction according to the ability of the solvent in the competency of polyphenols from Dayak onion bulbs.